Plasma-derived exosomal mRNA profiles associated with type 1 diabetes mellitus - Fan, Wenqi; Pang, Haipeng; Shi, Xiajie; Li, Jiaqi; Wang, Yimeng; Luo, Shuoming; Lin, Jian; Yu, Haibo; Xiao, Yang; Li, Xia; Huang, Gan; Xie, Zhiguo; et al. (Frontiers in Immunology, 2022)
Background Exosomes carry various types of transcripts, such as messenger RNAs (mRNAs), and play an important role in mediating cell-to-cell communication, thus influencing multiple physiological and pathological processes. However, the role of exosomal mRNAs in T1DM is largely unknown. Here, we aimed to identify the plasma-derived exosomal mRNA expression profiles in T1DM and to explore their potential biological functions in T1DM. Materials and Methods Plasma-derived exosomes were isolated from 10 patients with T1DM and 10 age- and sex-matched control subjects by size exclusion chromatography methods. Transmission electron microscopy, nanoparticle tracking analysis, and western blot analysis confirmed the presence of exosomes. The exosomal mRNAs were analyzed using the Illumina HiSeq platform. Six differentially expressed mRNAs (DEMs) were randomly selected to determine the expression level by quantitative real-time PCR (qRT−PCR) in a larger cohort (T1DM subjects N=40; control subjects N=40). The biological functions of DEMs were predicted by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Protein−protein interaction networks were constructed to explore the potential associations among DEMs. Results In total, 112 DEMs were identified in T1DM, among which 66 mRNAs were upregulated and 46 mRNAs were downregulated. Four of six candidate exosomal mRNAs were successfully validated by qRT−PCR. Bioinformatics analysis indicated that these mRNAs were most significantly involved in positive regulation by host viral transcription (GO enrichment analysis) and oxidative phosphorylation (KEGG pathway analysis). Conclusions Our study reported the plasma-derived exosomal mRNA expression profiles of T1DM for the first time. The identified DEMs might be associated with the pathogenesis of T1DM, and some DEMs have the potential to serve as biomarkers and therapeutic targets for T1DM.